Short-term exposure to air pollution and hospital admission for heart failure among older adults in metropolitan cities: a time-series study - Lee, Dong Wook; Han, Chang Woo; Hong, Yun Chul; Oh, Jong Min; Bae, Hyun Joo; Kim, Soontae; Lim, Youn Hee (International Archives of Occupational and Environmental Health, 2021)
Purpose: We aimed to investigate the association between air pollution concentration levels and hospital admissions for heart failure (HF) among older adults in metropolitan cities in South Korea. Methods: We used hospital admission data of 1.8 million older adults in seven metropolitan cities from 2008 to 2016, derived from the National Health Insurance Service of South Korea. Daily HF admission data were linked to air pollutants concentrations for the respective dates, including particulate matter less than 2.5 μm in size (PM2.5), 10 μm (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), and ozone. We estimated the association between air pollutants and daily HF admissions using quasi-Poisson generalized additive models for each city. Results: During the study period, 142,490 hospital admissions for HF were noted. Increases of 10 μg/m3 of PM2.5 and PM10, and 10 ppb of SO2, NO2, and CO were associated with an increased risk of HF admission by 0.93% ([95% confidence intervals 0.51–1.36], 0.55% [0.31–0.80], 6.04% [2.15–10.08], 1.10% [0.38–1.82], and 0.05% [0.01–0.09]), respectively, on the same day. Increases in mean exposure to PM2.5, PM10, and SO2 for 8 days from the concurrent day were also significantly associated with HF admissions. During the warm season, the risk of HF admissions increased shortly after an increase in PM2.5, whereas prolonged effects were observed during the cold season. Conclusion: Our study suggests the adverse effects of air pollution on HF. Moreover, the evidence of seasonality may help tailor protection guidelines for older adults.
Keywords: Air Pollutants; Air Pollution; Carbon Monoxide; Cities; Environmental Exposure; Heart Failure; Hospitalization; Humans; Nitrogen Dioxide; Ozone; Particulate Matter; Republic of Korea; Seasons; Sulfur Dioxide; Air pollution; Heart failure; Hospitalization; Older adults; Seasons